2010
DOI: 10.1364/oe.18.012065
|View full text |Cite
|
Sign up to set email alerts
|

3D In Vivo optical coherence tomography based on a low-voltage, large-scan-range 2D MEMS mirror

Abstract: In this paper we report the design, testing and use of a scannerless probe specifically for minimally invasive imaging of deep tissue in vivo with an epi-fluorescence modality. The probe images a 500 µm diameter field of view through a 710 µm outer diameter probe with a maximum tissue penetration depth of 15 mm specifically configured for eGFP imaging. Example results are given from imaging the pituitary gland of rats and zebrafish hearts with lateral resolution of 2.5 µm., "Real-time visualization of human pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
123
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(124 citation statements)
references
References 34 publications
1
123
0
Order By: Relevance
“…First, the scanning MEMS mirrors are operated by using electrostatic [25][26][27][28][29][30][31], electromagnetic [22,32], or electrothermal [33][34][35][36][37][38][39] actuation. An electrostatic force between suspending and fixed electrodes induces the electrostatic actuation, which allows a high scanning resonant frequency but it often requires high operational voltages.…”
Section: Actuation Mechanism Of Microscannersmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the scanning MEMS mirrors are operated by using electrostatic [25][26][27][28][29][30][31], electromagnetic [22,32], or electrothermal [33][34][35][36][37][38][39] actuation. An electrostatic force between suspending and fixed electrodes induces the electrostatic actuation, which allows a high scanning resonant frequency but it often requires high operational voltages.…”
Section: Actuation Mechanism Of Microscannersmentioning
confidence: 99%
“…The resonant frequencies of the mirror and frame actuator structures are 445 and 259 Hz, respectively. Sun et al also have reported a gimbal-less two-axis electrothermal MEMS mirror [37]. Four microactuators on each side increase a scanning area and satisfy lateral-shift-free design suspending the mirror plate (1 mm × 1 mm).…”
Section: Actuation Mechanism Of Microscannersmentioning
confidence: 99%
“…Modifications to the thermoelectric-bimorph structures can overcome this limitation by anchoring at the center of the mirror edges, as shown in Figure 2 [21].…”
Section: Thermoelectric Actuationmentioning
confidence: 99%
“…Their versatility further allows operation at resonance to achieve high-speed raster scanning, which is necessary for real-time en face imaging. Various MEMS scanning mirrors have been developed for beam steering in confocal microscopy [9][10][11][12][13][14], OCT [15][16][17][18][19][20][21], and two-photon microscopy [22]. In these micromirrors, 2D scanning motions can derive from thermoelectric, electrostatic, electromagnetic, or piezoelectric actuation, and the microfabrication adaptability of MEMS devices facilitates integration of additional functionality such as adjustable-focal-length scanning micromirrors [23] or dynamic aberration correction [24].…”
Section: Introductionmentioning
confidence: 99%
“…Microelectromechanical systems (MEMS) scanning mirrors are widely used in a variety of applications such as Fourier transform (FT) spectroscopy [1,2], confocal microscopy [3], optical coherence tomography [4,5], optical switches [6], and projection displays [7]. Scan range, speed, driving voltage, power consumption and footprint are among the key parameters for MEMS scanning mirrors.…”
Section: Introductionmentioning
confidence: 99%